2020
DOI: 10.1021/acs.nanolett.9b05086
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Excitons and Trions in MoSe2/WSe2 van der Waals Heterostructures

Abstract: Indirect excitons (IX) in semiconductor heterostructures are bosons, which can cool below the temperature of quantum degeneracy and can be effectively controlled by voltage and light. IX quantum Bose gases and IX devices were explored in GaAs heterostructures where an IX range of existence is limited to low temperatures due to low IX binding energies. IXs in van der Waals transition-metal dichalcogenide (TMD) heterostructures are characterized by large binding energies giving the opportunity for exploring exci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 91 publications
(195 reference statements)
3
61
0
Order By: Relevance
“…At each heterostack site, the overall multi-peak PL structure of HBL and HTL is mostly preserved upon the variation in the gate voltage (Supplementary Note 1) and excitation power down to 300 nW (Supplementary Note 3). Consistent with finite twist angle, the multi-peak PL of the HBL below 1.40 eV, with a peak separation of 30 meV between the two highest energy peaks and 15 meV between other consecutive peaks (Supplementary Note 3), is reminiscent of rich MoSe 2 -WSe 2 moiré spectral features 16 rather than of simple spectra from aligned HBLs [24][25][26][27][28][29] . Remarkably, the HTL PL, with a similar peak spacing of 15 meV, is strikingly similar to the cryogenic PL from native bilayer WSe 2 43 (Supplementary Note 4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…At each heterostack site, the overall multi-peak PL structure of HBL and HTL is mostly preserved upon the variation in the gate voltage (Supplementary Note 1) and excitation power down to 300 nW (Supplementary Note 3). Consistent with finite twist angle, the multi-peak PL of the HBL below 1.40 eV, with a peak separation of 30 meV between the two highest energy peaks and 15 meV between other consecutive peaks (Supplementary Note 3), is reminiscent of rich MoSe 2 -WSe 2 moiré spectral features 16 rather than of simple spectra from aligned HBLs [24][25][26][27][28][29] . Remarkably, the HTL PL, with a similar peak spacing of 15 meV, is strikingly similar to the cryogenic PL from native bilayer WSe 2 43 (Supplementary Note 4).…”
Section: Resultsmentioning
confidence: 98%
“…Despite numerous experimental and theoretical studies of MoSe 2 -WSe 2 HBLs, the origin of the lowestenergy PL remains a subject of debate 22 . While the majority of experimental studies interpret the HBL emission in terms of zeromomentum interlayer excitons with K or K 0 valley electrons and holes in MoSe 2 and WSe 2 15,16,19,21,[23][24][25][26][27][28][29] , others invoke excitons built from hybridized HBL conduction band states at Q pockets [30][31][32] , located roughly halfway between the center of the first Brillouin zone at Γ and K or K 0 valleys. Band structure calculations indeed suggest that hybridization of states near Q conduction band and Γ valence band of MoSe 2 and WSe 2 gives rise to strong energy renormalization upon HBL formation 2,33,34 which might turn either QK or QΓ interlayer excitons, composed of electrons at Q and holes at K or Γ, into the lowest-energy states.…”
mentioning
confidence: 99%
“…3,4 Several combinations of TMDs in a heterobilayer reveal a type-II band alignment resulting in spatially separated electron-hole pairs after optical excitation (so called charge-transfer or interlayer excitons). [5][6][7][8][9][10][11][12] Beside the choice of the materials, the relative orientation of the stacked layers can affect the interlayer coupling and the properties of the interlayer excitons. [13][14][15][16][17][18][19][20] Rotational misfit between two TMD monolayers results in a corresponding rotation of the hexagonal Brillouin zones and momentum-mismatched interlayer excitations.…”
mentioning
confidence: 99%
“…A reduced splitting of the IX emission lines of about 25 meV for MoSe 2 /WSe 2 heterobilayers is reported by Calman et al [96], by Hanbicki et al [97], and Ciarrocchi et al [54], respectively, with contrary interpretations. Calman et al explain the observed splitting due to neutral and charged interlayer excitons [96] in agreement with the interpretation for a IX doublet in a WSe 2 /MoSe 2 /WSe 2 structure [151]. Whereas Hanbicki et al interpret the IX doublet in terms of momentum indirect interlayer transitions between electron states hosted in the spin split conduction band at the Σ valley with hole states localized at the K WSe2 valley (see figure 5b) [97].…”
Section: Multivalley Physics Of Interlayer Excitonsmentioning
confidence: 88%
“…Baranowski et al used a very similar interpretation to explain the experimentally observed doublet structure in the photoluminescence from IX hosted by MoS 2 /MoSe 2 /MoS 2 tri-layer structure [98]. A reduced splitting of the IX emission lines of about 25 meV for MoSe 2 /WSe 2 heterobilayers is reported by Calman et al [96], by Hanbicki et al [97], and Ciarrocchi et al [54], respectively, with contrary interpretations. Calman et al explain the observed splitting due to neutral and charged interlayer excitons [96] in agreement with the interpretation for a IX doublet in a WSe 2 /MoSe 2 /WSe 2 structure [151].…”
Section: Multivalley Physics Of Interlayer Excitonsmentioning
confidence: 91%